Thermostability of the Mitoxantrone - DNA Complexes Irradiated by Non-Thermal Millimeter Electromagnetic Waves - A. T. Karapetyan; Yu. S. Babayan; M. A. Torosyan; M. A. Shahinyan
Thermostability of mitoxantrone complexes with DNA of sarcoma 45 and healthy rat liver earlier irradiated by non-thermal (50 μW/cm2) resonant (64.5 GHz and 50.3 GHz) and non-resonant (48.3 GHz) of water hexagonal structure frequencies millimeter electromagnetic waves (MEW) oscillations has been studied. It was shown that at irradiation of solutions by resonant with water hexagonalstructurefrequencies, a dehydration of nucleotides of irradiated DNA and Na+ ions existing in the solution occurs. At relatively low concentrations of mitoxantrone it results in decreasing of thermostability of complexes with DNA, moreover this change is more pronounced at complex-formation with DNA from sarcoma 45 tumor. It was shown that the thermostability of the radiated by non-resonant frequents DNA-MTX complexes does not change.
Keywords: Physics; Cross-Disciplinary